Value of Libraries: Relationships Between Provision, Usage, and Research Outcomes - Jubb, Michael; Rowlands, Ian; Nicholas, David (Evidence Based Library and Information Practice, 2013)
Objective – To explore the relationships in the United Kingdom between library expenditures, levels of usage, and research outcomes, focusing on the provision and use of e-journals. Methods – The project used a mixture of top-down and bottom-up approaches. It involved a close study of the behaviors of researchers in eight universities and two research institutes across a range of six subject areas, along with a parallel gathering and analysis of data for all U.K. universities and colleges, covering various library indicators together with data on article downloads and a range of measures of research performance. The work was undertaken in two stages and was completed in 2010. The first stage involved detailed mining of the publishers’ logs from Elsevier’s Science Direct and from Oxford Journals to generate fine-grained insights into the information-seeking behavior of scholars from the case study institutions, together with an initial analysis of the U.K.-wide data. The second stage involved a survey and interviews with a wide range of researchers as well as librarians from the case study institutions, together with further analysis of the U.K.-wide data. Results – Strong variations were found between users, not only in different disciplines but also in different institutions. Some, but not all, of the variations seemed to be related to the size and research intensity of the institution. Analyses of the U.K.-wide data show that levels of library expenditure influence subsequent levels of use of e-journals. While the modeling does not show strong direct linkages in either direction between library expenditure and research performance, it does show a strong positive feedback loop between the use of e-journals and research performance. Conclusion – There is a need both to broaden the focus beyond e-journals and for more detailed work to test hypotheses and understand the dynamics of the relationships between different variables over time.